Early results of full-endoscopic decompression of lumbar central canal stenosis by outside-in technique: A clinical and radiographic study. Issue 39 (1st October 2021) - Kim, Hyeun-Sung; Sharma, Sagar B.; Raorane, Harshavardhan D.; Kim, Kyeong-Rae; Jang, Il-Tae
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Retrospective cohort study. Full-endoscopic decompression of lumbar spinal canal stenosis is being performed by endoscopic surgeons as an alternative to micro-lumbar decompression in the recent years. The outcomes of the procedure are reported by few authors only. The aim of this paper is to report the clinical and radiographic outcomes of full endoscopic lumbar decompression of central canal stenosis by outside-in technique at 1-year follow-up. We reviewed patients operated for lumbar central canal stenosis by full endoscopic decompression from May 2018 to November 2018. We analyzed the visual analogue scale scores for back and leg pain and Oswestry disability index at pre-op, post-op, and 1-year follow-up. At the same periods, we also evaluated disc height, segmental lordosis, whole lumbar lordosis on standing X-rays and canal cross sectional area at the affected level and at the adjacent levels on magnetic resonance imaging and the facet length and facet cross-sectional area on computed tomography scans. The degree of stenosis was judged by Schizas grading and the outcome at final follow-up was evaluated by MacNab criteria. We analyzed 32 patients with 43 levels (M:F = 14:18) with an average age of 63 (±11) years. The visual analogue scale back and leg improved from 5.4 (±1.3) and 7.8 (±2.3) to 1.6 (±0.5) and 1.4 (±1.2), respectively, and Oswestry disability index improved from 58.9 (±11.2) to 28 (±5.4) at 1-year follow-up. The average operative time per level was 50 (±16.2) minutes. The canal cross sectional area, on magnetic resonance imaging, improved from 85.78 mm 2 (±28.45) to 150.5 mm 2 (±38.66). The lumbar lordosis and segmental lordosis also improved significantly. The disc height was maintained in the postoperative period. All the radiographic improvements were maintained at 1-year follow-up. The MacNab criteria was excellent in 18 (56%), good in 11 (34%), and fair in 3 (9%) patients. None of the patients required conversion to open surgery or a revision surgery at follow-up. There was 1 patient with dural tear that was sealed with fibrin sealant patch endoscopically. There were 10 patients who had grade I stable listhesis preoperatively that did not progress at follow-up. No other complications like infection, hematoma formations etc. were observed in any patient. Full endoscopic outside-in decompression method is a safe and effective option for lumbar central canal stenosis with advantages of minimal invasive technique.